Effects of foliar selenium spraying on the growth and selenium content and morphology of rice - Pei, Wenxia; Dai, Mengya; Shi, Sheng; Zhang, Yuan; Wu, Daxia; Qiao, Cece; Sun, Yafei; Wang, Jianfei (Frontiers in Plant Science, 2025)
Selenium (Se), an essential micronutrient for both plants and humans, plays critical roles in crop metabolism and human physiological functions. However, optimizing Se biofortification strategies to enhance grain Se accumulation while mitigating potential agronomic trade-offs remains a significant challenge. In this study, foliar applications of sodium selenite at concentrations of 0.0075 kg/hm² (FX01) and 0.015 kg/hm² (FX02) were administered during the full heading stage of rice (Oryza sativa L.) to systematically investigate Se uptake, interorgan translocation, and organic Se speciation in grains. Results demonstrated that foliar Se application significantly increased total Se contents and accumulation across rice tissues, with FX02 exhibiting superior enhancement compared to FX01. Specifically, total Se and organic Se contents in rice grains of FX02 were 2.76- and 2.77-fold compared to FX01, respectively. Translocation dynamics revealed that foliar treatment reduced Se transfer rates from leaves to husks and stems, while FX02 markedly improved phloem-mediated Se remobilization from leaves to grains. The Se translocation factor (TF) from leaves to grains increased to 0.71 under FX02, compared to 0.44 in FX01 and 0.60 in CK, indicating enhanced efficiency of Se redistribution under FX02. Spatial partitioning analysis further confirmed reduced Se retention in stems and husks alongside elevated accumulation in leaves under foliar treatments. Notably, Se accumulation in rice grains reached 24% under FX02, significantly higher than CK (15%) and FX01 (14%). Foliar Se application also increased the total organic Se and different organic Se forms contents in grains and altered its composition by reducing the proportion of RNA-bound Se. Temporal analysis revealed that total Se concentrations in rice tissues rose sharply within the first 14 days post-application, followed by a decline in vegetative tissues but a continued increase in grains after 31 days. In addition, grain Se enrichment showed no significant correlation with yield-related agronomic parameters. This study elucidates the dynamic transport-transformation mechanisms of foliar-applied Se in rice, providing a theoretical framework for designing precision Se biofortification strategies that synergistically improve grain nutritional quality and field adaptability.